PLC-based industrial application simulator: four ways traffic light management system - Rifin, Rozi; Kadiran, Kamaru Adzha; Hussin, Mohamad Zhafran; Dzulkifli, Muhammad Rajaei; Mat Saat, Ezril Hisham (Universiti Teknologi MARA, Kedah, 2023)
This paper introduces a state-of-the-art Programmable Logic Controller (PLC)-based simulator tailored for High Learning Education and Technical and Vocational Education and Training (TVET) institutions. The simulator aims to enhance the pedagogical approach to traffic light management systems by providing an immersive and interactive platform. Students can explore a 4-ways traffic light control system, applying theoretical knowledge practically in traffic management and automation. The simulator features a realistic traffic light intersection environment, an intuitive user interface, and interactive programming modules. Learners can engage in various traffic scenarios, analyze traffic flow, and develop advanced control strategies using PLC programming techniques. It covers different traffic management scenarios, including peak hours, emergencies, and pedestrian crossings, fostering comprehensive skills in managing complex traffic situations and optimizing flow for transportation system safety and efficiency. Instructors can monitor individual student progress, evaluate control logic designs, and provide personalized feedback through built-in assessment and performance tracking tools. The simulator also promotes teamwork and communication among learners through its support for multi-user collaboration. The PLC-based 4 ways traffic light control system simulator offers various benefits, including enhanced learning outcomes, cost efficiency (due to the elimination of physical traffic intersections), a safe learning environment, and industry-relevant skill development for contemporary urban planning demands. In conclusion, this article emphasizes the significance of the PLC-based simulator as an advanced educational tool for High Learning Education and TVET institutions. By facilitating practical and immersive learning experiences in traffic control and automation, the simulator equips learners to address real-world challenges in urban infrastructure and transportation management effectively.